The involvement of FATP1 regulating skeletal muscle fat deposition in stressed broilers was affected by fatty acid substrates - Wang, Minghui; Jiao, Hongchao; Zhao, Jingpeng; Lin, Hai; Wang, Xiaojuan (Frontiers in Veterinary Science, 2022)
Fatty acid transport protein 1 (FATP1), plays a major role in the transport and uptake of fatty acids into cells. The effect of FATP1 on the regulation of skeletal muscle fat uptake and deposition in stressed broiler chickens was investigated both in vivo and in vitro, and the effect of different fatty acid substrates were also included. Dexamethasone (DEX), a synthetic glucocorticoid (GCs), was employed to induce a hyper glucocorticoid milieu and simulate stress. The in vivo results showed that DEX would increase the mRNA expression of FATP1 and fat deposition in muscle tissues (P < 0.05), the very-low-density lipoprotein (VLDL) and insulin (INS) levels were significantly increased in the plasma by DEX (P < 0.05), and the mRNA levels of the glucocorticoid receptor (GR), adiponectin receptor (ADPNR) and peroxisomal proliferator-activated receptor α (PPARα) in thigh were also up-regulated by DEX (P < 0.05). In vitro experiment, DEX did not affect the myoblast fat deposition and PPARα and FATP1 expressions without the external fatty acid (P > 0.05). Under PA pretreatment, both myoblast fatty acid uptake and fat deposition were promoted by DEX treatment (P < 0.05), and the effects of DEX on the gene expressions of GR, ADPNR, PPARα and FATP1 were upregulated first and then downregulated as the dose of DEX increases; while under OA pretreatment, the myoblast fat deposition was not affected by DEX (P > 0.05), the fatty acid uptake was decreased by DEX at 500 nM compared to control (P < 0.05). When GR and PPARα were respectively inhibited by specific inhibitors RU486 and GW6471, the effects of DEX on fatty acid uptake were reversed for PA pretreated myoblasts (P < 0.05) but not for OA pretreated myoblasts (P > 0.05). These results indicates that FATP1 regulation by GCs was affected by fatty acid substrate - saturated fatty acids were favorable for fat uptake and deposition, while unsaturated fatty acids were not. GCs may affect the ADPNR-PPARα-FATP1 pathway by binding to its receptors, thus regulating the uptake of saturated fatty acids into myoblasts.